1992
DOI: 10.1093/cvr/26.9.871
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat modulation of left ventricular ejection fraction in the marmoset due to enhanced filling

Abstract: Dietary fish oil and sunflower seed oil increased the left ventricular ejection fraction in the marmoset monkey by enhancing ventricular filling, thus providing an energy sparing promotion of diastolic relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 0 publications
3
43
0
3
Order By: Relevance
“…16 Dietary n-3 PUFA reduced the susceptibility to arrhythmias in the present study, as in other studies. 10 -15 The reduced loss of K ϩ during ischemia may be indicative of effects on ion channels or exchange mechanisms that lead to changes in K ϩ conductance 26 and altered arrhythmic potential.…”
Section: Effects Of Dietary Lipids Onsupporting
confidence: 89%
See 1 more Smart Citation
“…16 Dietary n-3 PUFA reduced the susceptibility to arrhythmias in the present study, as in other studies. 10 -15 The reduced loss of K ϩ during ischemia may be indicative of effects on ion channels or exchange mechanisms that lead to changes in K ϩ conductance 26 and altered arrhythmic potential.…”
Section: Effects Of Dietary Lipids Onsupporting
confidence: 89%
“…In support of this premise, fish oil feeding increases left ventricular end-diastolic volume and ejection fraction in nonhuman primates and reduces rate pressure product, which may be indicative of low myocardial oxygen consumption (MVO 2 ). 16 We tested the hypothesis that n-3 PUFA incorporation into myocardial membranes has direct effects on heart function, particularly after ischemia, additional to previously reported effects on arrhythmia, thrombosis, and vascular function. We used the erythrocyte-perfused isolated working heart, which provides optimal oxygen delivery and permits assessment of hemodynamic function and metabolism under controlled physiologically relevant conditions.…”
mentioning
confidence: 99%
“…85 In addition, EPA and DHA may prevent the myosin heavy chain isoform α to β switch, a marker of HF and left ventricular hypertrophy. 86 Results of the Cardiovascular Health Study 87 seem to confirm in older adults the findings previously shown in nonhuman primates 88 of an association between fish intake and incremental stroke volume due to improvement of early and, possibly, late diastolic filling. Recently, chronic n-3 PUFA administration in athletes has been reported to reduce heart rate and oxygen consumption during exercise without a decrement in performance, in part due to improved energy production and utilization by cardiac myocytes.…”
Section: Cardiac Hemodynamics Cardiac Functionsupporting
confidence: 64%
“…8 In nonhuman primates, fish oil enhances left ventricular diastolic function. [9][10] In humans, fish oil supplementation lowers blood pressure, 11 reduces markers of systemic inflammation, 12 attenuates vasoconstrictive responses to angiotensin II, [13][14] improves arteriolar wall compliance, 15 and improves left ventricular diastolic filling. 16 Considerable epidemiological, clinical trial, and animalexperimental evidence also points to antiarrhythmic effects of n-3 fatty acids in fish, [17][18][19][20][21][22][23][24] which decrease excitability and cytosolic calcium fluctuations of ventricular myocytes via inhibition of Na ϩ and L-type Ca ϩϩ channels.…”
Section: Discussionmentioning
confidence: 99%